The Role of Organizational Culture in Improving Elementary Teachers' Professional Competence in Kempas, Indragiri Hilir - Siti Hartinah; Mada Sutapa (Journal of Education and Teaching Learning, 2026)
This study aims to analyze teacher professional competence, the factors influencing teacher professional competence, and the role of school organizational culture in supporting the improvement of teacher professional competence at SD Kecamatan Kempas, Indragiri Hilir District. Based on interviews with the principal and teachers, it was found that although teacher professional competence is generally good, challenges still exist regarding the mastery of technology and the limited time available to implement new teaching methods. Individual, organizational, and managerial factors significantly affect the development of teacher competence, while organizational culture that supports collaboration among teachers has proven to strengthen professional competence improvement. However, there are barriers related to limited access to training and insufficient facilities that need to be addressed. A more open and collaborative organizational culture, along with increased access to training, is essential to supporting the sustainable development of teacher competence. This study is expected to contribute to more effective management of organizational culture in other schools